THE BEHAVIOR OF TAXPAYERS AND THE OPTIMAL STRATEGY OF THE TAX AUDIT STRATEGIC PRIORITIES FOR IMPROVING TAXATION OF REAL ESTATE PROPERTY - L. Kardanova; V. Kuzmenko (Вестник Северо-Кавказского федерального университета)
The article discusses the solution to the problem of improving the efficiency ofproperty taxation based on the optimization of the current system of tax benefits. It has been proved that the provision of tax deductions based on the area of taxable property does not comply with the principle of social orientation of state policy, tso nce the owners of expensive and elite real estate bear the minimum tax burden, and also reduces the tax base municipalities. To solve this problem, it was proposed to establish a progressive taxation scale and provide x beneits on an address basis calculated on the basis of the cadastral value of the property.